Pengaruh Pelaksanaan Shalat Dhuha terhadap Kecerdasan Spritual Santri Kelas VIII di Mts S Pondok Pesantren Al-Muttaqin Balai Belo, Koto Kaciak, Maninjau - Yulia Rahman; Salmi Wati; Arifmiboy Arifmiboy; Iswantir Iswantir (Journal on Education, 2023)
This study aims to find out how the teacher's personality competence is described at MTs S PP Al-Muttaqin Balai Belo, how is the student learning motivation described at MTs S PP Al-Muttaqin Balai Belo and whether there is a significant effect of the Akidah Akhlak teacher's personality competence on students' learning motivation Akidah Akhlak. This research is a quantitative descriptive study conducted at MTs S PP Al-Muttaqin Balai Belo using the correlation method and simple linear regression analysis, namely measuring the influence of an independent (independent) variable on a dependent (dependent) variable using manual calculations with M. S Excel and SPSS programs. The data collection technique used is by using a questionnaire. The population in this study were 70 students at MTs S PP Al-Muttaqin Balai Belo, because the population was less than 100, the authors took all of the population as the research sample, namely 70 students. In the results of the study, it was obtained an overview of the competence of aqidah moral teachers at MTs S PP Al-Muttaqin Balai Belo which was included in the high category with a proportion of 73% and the description of students' learning motivation was included in the high category with a proportion of 64% answers. From the results of the study it can be interpreted that there is a significant influence between the X variable simultaneously on the Y variable where it is known that the t count is 6.705 > t table 1.997 and the regression F is 44.953 > F table 3.98, and the sig. Regression 000 <0.05 which means H1 is accepted while Ho is rejected. So from the title the effect of the personality competence of the Akidah Akhlak teacher on the learning motivation of Santri at MTs PP Al-Muttaqin Balai Belo has a significant influence.